Effects of Replacement Cold Press Poppy Seed (Papaver somniferum) Oil to Fish Oil at Different Proportions on the Growth Performance, Blood Parameters, and Digestive Tracks Histopathology in Juvenile Common Carp (Cyprinus carpio) - Kesbiç, Osman Sabri; Acar, Ümit; Demirci, Beste; Terzi, Funda; Tezel, Rifat; Türker, Ali; Güllü, Kenan; Erol, Hüseyin Serkan (Wiley, 2023)
The major goal of the study is to determine the potential use of poppy seed oil as a main lipid source in common carp diets. To investigate this, five different experimental diets (PO0, PO25, PO50, PO75, and PO100) with various proportions of fish oil and poppy seed oil blended as oil sources were provided and supplied to common carp for 90 days. In triplicate groups of 60 fish, 300 common carp weighing 1.15 ± 0.06 g were randomly placed in 100 L aquariums. At the end of the feeding trial, blood and tissue samples were collected from the fish after gravimetric measurements of the fish. The growth and feed utilization performance of the fish were calculated by gravimetric measurements, and tissue samples were examined by hematological, micromorphometric, and histopathological methods. According to the results, poppy seed oil enhanced the quantity of linoleic acid (18 : 2 ω−6) in the diet, and fish fed with the diet consisting completely of poppy seed oil (PO100) had the significantly greatest growth and feed utilization performance ( P < 0.05 ). Furthermore, no significant differences in hematological or liver pathology were detected between all groups that were fed with experimental diets ( P > 0.05 ). However, as compared to the control group, the digestive system micromorphometry and histomorphometric measurements of the fish fed with PO100 group diets showed a significant increase ( P < 0.05 ). In conclusion, it was determined that the carp fed with feeds produced by using only poppy oil as the main fat source improved their digestive system, growth, and feed utilization performance without any negative effects.
Keywords: Seed oil